(3OjhGf GdCOHs - (3ESMGb Hf EHQGgje Hf GdMSjf GdaGQGHqj, CHh EHQGgje, J (B350 (3g` s
(3ChdgG (B:s
(3bGd GdTjN CHh GHQGgje GdMeO ddg eMeOkG jHdZ QVGg hjeJQi GdeQjO efg CeG HYO aEf Gddg bOQ GdCTjGA HbOQJg s
(3BNQgG (B:s
(3GdGQLMfGf Gdejd GfbVi cJGH GdSGde Hef Gddg hMSHfGGddg hfYe Gdhcjd s
(3GdfSNI HgG MhGTs
(3YdjgG ebGHdI Ydi fSNI GHf QRjf SfI (B618 (3hJedc SfI (B926s
(3cJH HNW ajg HYV GdVHWs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B293s
(3JHUQGJ GdCUd (B:s
Keywords: (3GddZIs